Educational Empowerment through Teacher Speech Acts in The Ron Clark Story: A Pragmatic Analysis - Fiqriatul Fadillah; Mardiyanah Nasta; Fivi Faila (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2026)
This study examines how educational empowerment is represented through teacher speech acts in the film The Ron Clark Story. The study is significant because teacher language functions not only as a medium of instruction but also as a pedagogical resource that can support students’ psychological, academic, and social development. Using a qualitative descriptive design and a pragmatic approach, this study analyzed 13 teacher utterances selected from classroom interaction scenes in the film. The data were analyzed using speech act theory, teacher talk concepts, and an educational empowerment framework. The findings reveal that educational empowerment is represented through representative, directive, expressive, commissive, and declarative speech acts. These speech acts function pedagogically to provide emotional support, encourage learning engagement, promote self-reflection, and foster social belonging within the classroom community. The findings further indicate that different speech acts contribute to different dimensions of empowerment depending on the communicative goals of the teacher and the needs of learners. This study contributes to educational pragmatics by demonstrating that teacher speech acts function not only as linguistic actions but also as pedagogical resources that support educational empowerment in classroom interactions represented in film narratives.